Plan de mejora de la calidad en el proceso de secado de maíz mediante la aplicación de la metodología six sigma - Padilla Zamora, Kevin Valentin (2022)
The purpose of this research project is to develop a "Plan for quality improvement in the corn drying process through the application of the Six Sigma methodology", identifying in the first place the activities that this production process entails, which allowed elaborate process and route flow diagrams, later each of the 7 types of shedding or waste of a company was analyzed, establishing that one of the most considerable waste of final product occurs in the decreases in the final mass of the grain in the over-process moult, since, if a corn with excessive moisture (34%) and a high content of impurities (5%) is received, a mass of 800qq can reduce up to 27.20% (217.7qq), this if it reaches 13% moisture and 1% impurities established by the INEN standard for corn marketing. By means of an Ishikawa diagram, the causes that generate the damage of the corn in the drying process were established, to later be classified by Pareto where 80% of the quality problems that occur in the process are due to the presence of pests and rodents, excess humidity at the time of reception and a high content of impurities. For the development of the last result, the Six Sigma DMAIC methodology was implemented in each of its phases, which are Define, Measure, Analyze, Improve and Control, applying different Lean Manufacturing tools, resulting in the approach of three improvement proposals for the corn drying process, with the aim of reducing the statistical variability that exists in the process, in addition to the design of a Dashboard proposal that allows periodic monitoring of the data generated daily in the marketers. Keywords: Six Sigma, Mudas, Improvement Plan, Methodology.